Two-Component Scattering Decomposition Technique for Walk-Through Security Scanners Using a Copolarized-MIMO Array - Root, Konstantin; Ullmann, Ingrid; Vossiek, Martin (2024 21st European Radar Conference, EuRAD 2024, 2024)
The widespread deployment of walk-through security scanners necessitates high reliability and a minimal false-alarm rate. This paper proposes a novel approach to improve existing systems by distinguishing between two scattering processes encountered during security checks: reflections from skin versus reflections from concealed objects. As skin shows specular reflection behavior, whereas objects tend to reflect diffuse, reconstruction results of the same scene with different array geometries show different imaging results. Therefore, we separate the imaging array into multiple partial arrays that exploit this scattering behavior beneficially. After obtaining the different reconstruction images, we propose an image processing technique that allows to obtain information about object reflections in the scene. This technique uses existing state-of-the-art walk-through scanners without the need for hardware modifications and hence, can easily be integrated. We validate the efficiency of this approach through realistic measurements involving human subjects and various threat objects. Our results demonstrate the capability to detect these objects, offering promise to improve existing systems.
CRIS-Team Scopus Importer:2024-12-13
Keywords: MIMO radar; personnel screening; radar imaging; scattering decomposition; security scanning